THE ROLE OF GIS TECHNOLOGIES AND GRAPHIC INTERFACES IN ENGINEERING PROJECTS - Mashrapova Gulbakhor Mamasaliyevna (Modern American Journals, 2025)
This article analyzes the evolving role of Geographic Information Systems (GIS) technologies and graphic interfaces in engineering projects, with a special focus on applications in Uzbekistan and the broader global context. Through a review of scientific literature, case studies, and expert interviews, the study demonstrates how the integration of GIS and user-friendly visualization tools enhances spatial analysis, scenario modeling, decision support, and stakeholder communication in engineering workflows. Key findings reveal substantial improvements in project planning efficiency, risk management, and transparency, although challenges remain in areas such as training, interoperability, and digital infrastructure. The article concludes that GIS and graphic interfaces are indispensable for modern, adaptive engineering practice, calling for continued investment in digital skills, data quality, and cross-sector collaboration.
Keywords: GIS; engineering projects; graphic interfaces; spatial analysis; data visualization; decision support; project management; digital transformation; Uzbekistan; infrastructure planning.